2018
DOI: 10.1002/uog.19040
|View full text |Cite
|
Sign up to set email alerts
|

Addition of N‐terminal pro‐B natriuretic peptide to soluble fms‐like tyrosine kinase‐1/placental growth factor ratio > 38 improves prediction of pre‐eclampsia requiring delivery within 1 week: a longitudinal cohort study

Abstract: The addition of NT-proBNP assessment improves the short-term prediction of delivery as a result of PE compared with sFlt-1/PlGF ratio alone, when the sFlt-1/PlGF ratio is > 38. This finding should be considered in future research on the assessment of short-term risk of delivery as a result of PE. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…However, although PIERS and PREP are of value in established cases of PE, considerable clinical resources are expended monitoring women considered to be at high risk of PE. This issue contains several publications demonstrating the added clinical value of repeat soluble fms‐like tyrosine kinase‐1 (sFlt‐1):PlGF ratio testing and use of additional (N‐terminal pro‐B natriuretic peptide (NT‐proBNP) and C‐terminal pro‐endothelin‐1 (CT‐pro‐ET1)) biomarkers in the high‐risk population. Whilst these are encouraging clinical findings, it is important to bear in mind that, as for early‐pregnancy PE screening tests, combining biochemical and biophysical markers may allow for even better prediction of adverse pregnancy outcome.…”
Section: Prognostic Markers In Pre‐eclampsiamentioning
confidence: 99%
“…However, although PIERS and PREP are of value in established cases of PE, considerable clinical resources are expended monitoring women considered to be at high risk of PE. This issue contains several publications demonstrating the added clinical value of repeat soluble fms‐like tyrosine kinase‐1 (sFlt‐1):PlGF ratio testing and use of additional (N‐terminal pro‐B natriuretic peptide (NT‐proBNP) and C‐terminal pro‐endothelin‐1 (CT‐pro‐ET1)) biomarkers in the high‐risk population. Whilst these are encouraging clinical findings, it is important to bear in mind that, as for early‐pregnancy PE screening tests, combining biochemical and biophysical markers may allow for even better prediction of adverse pregnancy outcome.…”
Section: Prognostic Markers In Pre‐eclampsiamentioning
confidence: 99%
“…Sugulle et al 6 measured MR-proANP at 24 to 42 weeks' gestation in 77 normotensive and 107 PE pregnancies and found that MR-proANP had an AUC of 0.85 in discriminating between PE pregnancies and normotensive pregnant controls, which was inferior to that of sFlt-1 (AUC, 0.94). In contrast to copeptin and MR-proANP, another cardiovascular biomarker, N-terminal pro-B natriuretic peptide (NT-proBNP), has shown incremental value in predicting short-term delivery due to PE 19 when added to sFlt-1/PlGF ratio > 38. Similarly, a recent study demonstrated that adding NT-proBNP > 174 pg/mL to an sFlt-1/PlGF ratio > 45 increases significantly the positive predictive value of sFlt-1/PlGF ratio 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research [25][26][27] has described the added value of repeat testing of soluble fms-like tyrosine kinase-1 (sFlt-1)/placental growth factor (PlGF) ratio, alone or with N-terminal pro B-type natriuretic peptide or C-terminal proendothelin-1 biomarkers, in the follow-up of pre-eclampsia. Both sFlt-1 and PlGF are produced by the placenta.…”
Section: Evidence Of Maternal Cardiovascular Maladaptation and Pre-ecmentioning
confidence: 99%